A Study of the Ability of Pseudomonas KK5 in Utilization of Methanol as a Sole Source of Carbon and Energy and the Role of its Plasmid. - القزاز عبد الكريم; الشمري رنا; رستم هديل (Iraqi Journal of Science, 2025)
Fifty different samples (water and soil) were collected from different places in Iraq. Only (5) isolates showed the ability to grow and utilize methanol as a sole source of carbon and energy. Morphological, cultural characterization and biochemical tests confirmed that these isolates belonging to genus Pseudomonas (KK1-KK5) .Plasmid profiles results showed that these isolates were harbored only one large plasmid . KK5 isolate was selected because of its efficiency and ability to grow in high density on methanol selective medium (0.8%) for conjugation and curing experiments, these were checked by conjugation experiments after their expression in E. coli MM294. The genes responsible for methanol utilization were located on large conjugative plasmid. These results were confirmed by data obtained from curing experiments.